Analysis of Parking Needs and Arrangements in the Pulau Datok Beach Tourism Area in Sukadana - Alqadri, Istiqomah; Kadarini, S. Nurlaily; Azwansyah, Heri (Fakultas Teknik Universitas Tanjungpura, 2025)
Pantai Pulau Datok in Sukadana is one of the region